2014
DOI: 10.1037/a0035507
|View full text |Cite
|
Sign up to set email alerts
|

The role of time on task in computer-based low-stakes assessment of cross-curricular skills.

Abstract: The role of time on task (TOT) for students' attainment in a low-stakes assessment of cross-curricular skills was examined using the log data collected in the computer-based assessment (CBA). Two structural equation models were compared: Model 1, in which students' test scores were explained by grade point average (GPA) together with mastery and detrimental motivational attitudes, and Model 2, in which TOT was added to the model to mediate the effects of GPA and the 2 motivational constructs. Fitting the model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 67 publications
2
30
0
1
Order By: Relevance
“…This idea is in line with Goldhammer and Klein Entink's (2011) study, in which time on task was related only to the behavioral component of executive attention, which was found to further direct students' goal orientations (Bipp et al, 2012). Kupiainen et al (2014) came to the same conclusion by showing that goal orientations determined the amount of time students were ready to invest in cross-curricular tasks.…”
Section: Relations Among Covariates Cps Time On Task and Cps Abilitysupporting
confidence: 69%
See 2 more Smart Citations
“…This idea is in line with Goldhammer and Klein Entink's (2011) study, in which time on task was related only to the behavioral component of executive attention, which was found to further direct students' goal orientations (Bipp et al, 2012). Kupiainen et al (2014) came to the same conclusion by showing that goal orientations determined the amount of time students were ready to invest in cross-curricular tasks.…”
Section: Relations Among Covariates Cps Time On Task and Cps Abilitysupporting
confidence: 69%
“…From a conceptual perspective, given that orientations reflect students' effort and investment in solving tasks, one might assume that time on task and goal orientations are linked. This assumption was strengthened by Kupiainen et al's (2014) recent study, which was concerned with the effects of goal orientations on time on task and learning in cross-curricular contexts. They found that students' goals directed their efforts in spending time for solving tasks and learning.…”
Section: Research Question 2: Determinants Of Cps Time On Task and Cpmentioning
confidence: 91%
See 1 more Smart Citation
“…Furthermore, the time participants spent on tasks was taken into account as an indicator of engagement for processing the feedback and thus for students' commitment to the tasks (Guthrie et al, 2004). Findings from low-stake and non-timed performance testing suggested a positive relationship between response times and performance outcomes, even when prior ability is taken into account (Kupiainen, Vainikainen, Marjanen, & Hautam€ aki, 2014). For reading tests, a slightly positive effect of time-on-task was found for demanding reading situations (Goldhammer et al, 2014).…”
Section: The Present Studiesmentioning
confidence: 97%
“…Az OECD PISA digitális olvasás-szövegértés vizsgála-tában például a tanulók teljesítményét a tesztmegoldással töltött idővel jellemezték (OECD, 2011), de e speciális háttérváltozó elemezésekbe történő bevonása az újabb munkákban is megjelenik (l. pl. Kinyó, megjelenés alatt;Vainikainen, Marjanen és Hautamäki, 2013, Vidákovich, 2014.…”
Section: A Számítógép Alapú Mérés-értékelés Lehetőségeiunclassified